Writing the Time of Troubles - Morris, Marcia A. (Academic Studies Press, 2018)
Is each moment in history unique, or do essential situations repeat themselves? The traumatic events associated with the man who reigned as Tsar Dmitry have haunted the Russian imagination for four hundred years. Was Dmitry legitimate, the last scion of the House of Rurik, or was he an upstart pretender? A harbinger of Russia's doom or a herald of progress? Writing the Time of Troubles traces the proliferation of fictional representations of Dmitry in eighteenth- and nineteenth-century Russia, showing how playwrights and novelists reshaped and appropriated his brief and equivocal career as a means of drawing attention to and negotiating the social anxieties of their own times
10.1515/9781618118646
Keywords: Kings and rulers in literature; Russian literature / 18th century / History and criticism; Russian literature / 19th century / History and criticism; False Dmitry; Historical formalism; Historical poetics; Literature and law; Russian historical drama; Russian historical novels; Time of Troubles; Trauma narratives; Russisch; Literatur; LITERARY CRITICISM / Russian & Former Soviet Union